The Role of Latently Infected B Cells in CNS Autoimmunity - Márquez, Ana Citlali; Horwitz, Marc Steven (Frontiers in Immunology, 2015)
The onset of Multiple Sclerosis is caused by both genetic and environmental factors. Among the environmental factors, it is believed that previous infection with Epstein Barr Virus (EBV) may contribute in the development of MS. EBV has been associated with other autoimmune diseases such as Systemic Lupus Erythematous (SLE) and cancers like Burkitt’s lymphoma. EBV establishes a life long latency in B cells with occasional reactivation of the virus throughout the individual’s life. The role played by B cells in MS pathology has been largely studied, yet is not clearly understood. In MS patients, Rituximab, a novel treatment that targets CD20+ B cells, has proven to have successful results in diminishing the number of relapses in remitting relapsing MS, however the mechanism of how this drug acts has not been clearly established. In this review we analyze the evidence of how B cells latently infected with EBV might be altering the immune system response and helping in the development of MS. We will also discuss how animal models such as Experimental Autoimmune Encephalomyelitis (EAE) and murine gammaherpesvirus-68 (γHV-68) can be used as powerful tools in the study of the relationship between EBV, MS, and B cells.